Clinical features and nursing strategies of reexploration for hematomas after thyroid surgery: insights from a 7-year single-center study in China - Xiuting Zhang; Benling Hu; JiayuXiao; Xuesong Zhang; Jingya Zhang; Liqin Zhu; Yanbing Kuang; Zhiheng Huang; Yujing Weng (BMC Surgery)
Abstract Objective To explore clinical characteristics of postoperative hemorrhage following thyroid or parathyroid surgery, and to discuss the nursing strategies for its prevention. Methods A retrospective analysis was conducted on all patients who underwent thyroid or parathyroid surgery from February 2016 to September 2023. The clinical data of patients who experienced postoperative hemorrhage and required reoperation were collected and analyzed. Results Among the 5579 patients who underwent surgery, 42 patients experienced postoperative hemorrhage and required reoperation. Hemorrhage occurred within 6 h in 19 cases (45.2%) and within 24 h in 35 cases (83.3%). The most common bleeding sites were the anterior cervical muscle group (44.2%) and branches of the superior or inferior thyroid artery (20.9%). Underlying diseases such as hypertension, diabetes, hemophilia, and postoperative activities like neck movements, coughing, vomiting, and drainage tube manipulation were potential risk factors for postoperative hemorrhage. Clinical manifestations of postoperative hemorrhage included neck swelling or tightness, increased drainage fluid with clots, incision bleeding, pain, skin bruising, and worsening dyspnea. Conclusion Understanding the potential risk factors and characteristics of postoperative hemorrhage in thyroid surgery is crucial for specialized thyroid nursing care, as it can aid in its prevention and treatment.